Analyzing socio-affectivity in preschool children’s interactions with the Aquarela Virtual System - Luã Marcelo Muriana, Emanuel Felipe Duarte, Maria Cecília Calani Baranauskas, Josiane Rosa de Oliveira G. Pimenta and Yusseli Lizeth M. Mendoza (Educational Technology & Society)
Within the enactive perspective to cognition, the sense-making process takes place from the subject’s action-perception in a world. Social relationships and emotional factors seem to play an active role in this process. In this paper we analyze the socio-enactive experience of preschool children along their interaction with the Aquarela Virtual, a system designed under a phenomenological perspective, mixing concrete and virtual elements. The recorded data consists of system logs of interaction, particularly those related to the use of emojis representing emotional states and the photos that children took during their interaction with the system. Additionally, transcripts of video recordings from the activity, which captured the children’s speech, actions, and behaviors, were used in a thematic analysis. Results illustrate the socio-affective aspects of the interaction with the system, how the socio-affectivity manifests itself, and how they affect the users’ meaning-making. In this work, we illustrate the use of emojis to express emotions during the interaction with the system and how they influence the socio-affectivity among users because of the social perception, or the lack of it. Results show the socio-affective perception has an impact on individual behavior and on the group of users of the system. Moreover, even a virtual environment, with users physically distant from each other and with remote access, can afford the socio-affectivity among the participants. As possible implications the work suggests that incorporating more dynamically responsive emotional elements to educational technologies could enhance engagement and emotional understanding among preschoolers.